Reflectance response of optical fiber coated with carbon nanotubes for aqueous ethanol sensing - Shabaneh, Arafat Abdallah Abdelwadod; Girei, Saad Hayatu; M. Thirunavakkarasu, Punithavathi; Abdul Rashid, Suraya; Yunusa, Zainab; Mahdi, Mohd Adzir; Paiman, Suriati; Ahmad, Muhammad Zamharir; Yaacob, Mohd Hanif (Institute of Electrical and Electronics Engineers, 2014)
Ethanol is a highly flammable chemical and is widely used for medical and industrial applications. In this paper, optical sensing performance of aqueous ethanol with different concentrations is investigated using multimode fiber coated with carbon nanotubes (CNT). The multimode optical fiber tip is coated with CNT via a drop-casting technique and is annealed at 70 °C to improve the binding of the nanomaterial to the silica fiber. The optical fiber tip and the CNT sensing layer are microcharacterized using field emission scanning electron microscopy, Raman spectroscopy, and X-ray diffraction techniques. The reflectance response of the developed fiber sensor is measured using a spectrophotometer in the optical wavelength range of 500-800 nm. Upon exposure to ethanol with concentration ranges of 5%-80%, the sensor reflectance reduced proportionally. The dynamic response decreased by 4% when the sensor is exposed to ethanol with concentration of 80% in distilled water. It is found that the sensor shows fast response and recovery as low as 38 and 49 s, respectively.